THE ROLE OF ARTIFICIAL INTELLIGENCE UTILIZATION ON STUDENTS' SELF-CONFIDENCE THROUGH KNOWLEDGE AND MOTIVATION - Lidyawati; Bakri Hasanuddin; Wiri Wirastuti; Nur Risky Islianti (RADJA PUBLIKA, 2026)
Advances in artificial intelligence (AI) have transformed the way students acquire information and supported the learning process. However, the impact of AI use on students’ self-confidence through knowledge and motivation still requires further study. This study aims to analyze the effect of artificial intelligence on students’ self-confidence, with knowledge and motivation serving as mediating variables. This study employed a quantitative approach involving 292 students from the Faculty of Economics and Business at Tadulako University, selected using the proportionate stratified random sampling technique. Data analysis was conducted using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method with the SmartPLS 4 software. The results of the analysis indicate that artificial intelligence has a positive and significant effect on students’ knowledge, motivation, and self-confidence. Knowledge does not have a significant effect on students’ self-confidence. Motivation has a positive and significant effect on students’ self-confidence. The results of the mediation test indicate that knowledge does not mediate the effect of artificial intelligence on students’ self-confidence. The mediation test results also showed that motivation mediates the effect of artificial intelligence on students’ self-confidence. These findings indicate that the use of artificial intelligence can support the improvement of students’ self-confidence and provide insights for higher education institutions in optimizing the use of artificial intelligence in the learning process.